E-delivery in local government - Kotyla, Cyryl (E-doręczenia w samorządzie lokalnym, 2020)
The study constitutes an original discussion of the consequences of the eIDAS Regulation, with regard to the electronic delivery of official correspondence by local government units. The main purpose of the study is to verify the thesis that electronic delivery will become the primary manner of official correspondence delivery in Poland, which requires functional and organizational changes as well as financial outlays in the initial period, and, at the same time, will provide measurable savings for units in the public finance sector. Supplementary research objectives involve estimation of the term perspective for the introduction of e-delivery in Poland and an examination of the degree of administrative offices’ IT preparation for the implementation of e-delivery. The research methods used include literature research, the method of legal-regulation analysis, case study and own observations. As a result of the analyses carried out, it was found that an Act on electronic delivery is to enter into force as early as October 2020 and, according to its current shape, local governments will be obliged to implement e-delivery, starting from January 1, 2024. Inauspiciously, the current level of local governments’ preparation for the implementation of e-delivery is insufficient and requires the introduction of IT systems for electronic documentation management as well as organizational and functional changes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 143-159
Keywords: eIDAS; e-delivery; e-document; e-signature; local government; elektroniczne doręczenia; e-dokument; e-podpis; samorząd lokalny